The Imine‐Based COF TpPa‐1 as an Efficient Cooling Adsorbent That Can Be Regenerated by Heat or Light. Issue 39 (3rd September 2019) - Pérez‐Carvajal, Javier; Boix, Gerard; Imaz, Inhar; Maspoch, Daniel
Abstract: Adsorption‐based cooling systems, which can be driven by waste heat and solar energy, are promising alternatives to conventional, compression‐based cooling systems, as they demand less energy and emit less CO2 . The performance of adsorption‐based cooling systems relates directly to the performance of the working pairs (sorbent–water). Accordingly, improvement of these systems relies on the continual discovery of new sorbents that enable greater mass exchange while requiring less energy for regeneration. Here, it is proposed that covalent‐organic frameworks (COFs) can replace traditional sorbents for adsorption‐based cooling. In tests mimicking standard operating conditions for industry, the imine‐based COF TpPa‐1 exhibits a regeneration temperature below 65 °C and a cooling coefficient of performance of 0.77 – values which are comparable to those reported for the best metal–organic framework sorbents described to date. Moreover, TpPa‐1 exhibits a photothermal effect and can be regenerated by visible light, thereby opening the possibility for its use in solar‐driven cooling. Abstract : The imine‐based covalent‐organic framework TpPa‐1 is proposed as an adsorbent for cooling systems. TpPa‐1 can be regenerated upon heating at temperatures present in cogeneration plants (<65 °C) or when exposed to visible light and shows a high value for cooling coefficient of performance of 0.77.